Pengaruh Struktur Hutang, Struktur Aktiva dan Struktur Modal Terhadap Kinerja Perusahaan Pada Perusahaan Tekstil Dan Garment Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2018 - Rahmat Hidayat; suhardi suhardi; Alam Surya Wijaya (JEM Jurnal Ekonomi dan Manajemen, 2019)
The study aims to determine the effect of debt structure, assets structure and capital structure on firm performance in the manufacturing companies sub-sector textile and garment listed on the Indonesia stock exchange in 2015-2018. The research uses a quantitative method. Sampling technique in this research is purposive sampling technique. The sample in this research is as many as 10 companies in the period of 4 years. The analysis technique used in research is logistic regression analysis using Eviews 4.1 software. The research result shows that debt structure has a negative effect on firm performance, assets structure has no effect on firm performance, and capital structure has a positive on firm performance. In the study was organized to add variables or to do research to other industries